Incidence of using chicken fat based biodiesel on the performance of a 13.5 kW compression ignition piston engine for power generation - Sierra Vargas, Fabio Emiro; Montenegro, Manuel Antonio; Narváez Argoty, Favio Orlando (TECCIENCIA, 2015)
New alternatives and feedstocks have been identified to overcome the impact caused by combustion of fossil fuels; some of them point on the promotion of second, third and fourth generation biofuels resulting from non-edible crops and other raw materials. The lack of information about the performance of engines used for power generation encumbers the use of chicken fat biodiesel in gensets in rural areas or other applications in which power generation is the main purpose. Therefore, this work aims to identify the incidence of using chicken fat biodiesel on the performance of a 13.45kWe internal combustion engine employed for power generation. The biodiesel was synthesized in lab conditions and afterwards fueled in the engine. Parameters such as the total electrical efficiency, heat rate, fuel consumption and the exhaust gas emissions are analyzed. A Lister TR2 diesel engine fixed to a Leroy Soner LSA 38 M/J electrical generator was employed. The chicken fat biodiesel was successfully produced in a lab-scale facility and afterward employed as biofuel blended with commercial biodiesel BPa7. The efficiency of the genset increases up to 38.79% with B22.5 higher than the 35.08% obtained for B0. As a consequence of the fuel reduction and addition of a sustainable biofuel such as chicken-fat biodiesel the carbon footprint was also decreased; the CO2 released decreases about 2.9 kgCO2h-1 when the genset was operating at full capacity fueled with B22.5.